Experimental methods for estimation of plant fitness costs associated with herbicide-resistance genes - Vila Aiub, Martin Miguel (2015)
Since the beginning of agriculture, crops have been exposed to recurrent invasion by weeds that can impose severe reductions in crop quality and yield. There have been continuing efforts to reduce the impacts of weeds on production. More than 40 yr ago, overreliance on herbicide technology to reduce weed infestations resulted in the selection of adaptive traits that enabled weed survival and reproduction under herbicide treatments. As a result, herbicide resistance in > 200 weed species has evolved worldwide.